Polybenzimidazole-crosslinked-poly(vinyl benzyl chloride) as anion exchange membrane for alkaline electrolyzers. (September 2020) - Coppola, R.E.; Herranz, D.; Escudero-Cid, R.; Ming, N.; D'Accorso, N.B.; Ocón, P.; Abuin, G.C.
Abstract: Zero-gap liquid alkaline water electrolyzers have great potential for hydrogen production. In order to enhance their actual performance, one of the key components to investigate is the anionic exchange membrane that allows the conduction of anions between the electrodes. This paper reports the preparation and characterization of membranes composed of a polybenzimidazole, either poly(2, 5-benzimidazole) (ABPBI) or poly[2-2′-(m-phenylene)-5-5′-bibenzimidazole] (PBI), crosslinked with different ratios of poly(vinylbenzyl chloride) (PVBC), forming thermally stable and homogeneous films. Quaternization of these films with 1, 4-diazabicyclo (2.2.2) octane (DABCO) followed by immersion in an alkaline solution lead to the introduction of quaternary ammonium groups and hydroxide anions respectively. Adequate thermal stability is observed in the temperature range of application (below 100 °C). Measurements of KOH and water and related swelling reflect the higher absorption capacity of ABPBI based membranes relative to PBI based ones. ABPBI-c-PVBC/OH 1:2 membranes at 50 °C are characterized by high ionic conductivity values (48 mS cm −1 ), reaching 380 mA cm −2 at cell voltage 1.98 V. In conclusion, we consider that these membranes are competitive candidates as anion exchange membranes for zero-gap alkaline water electrolyzers, and can be further enhanced to reach the performance of state of the art AEM's. Graphical abstract: Image 1 Highlights: Quaternized and crosslinked ABPBI-PVBC membranes are stable and homogeneous. ABPBI-PVBC have higher density of QA sites, KOH uptake and conductivity than PBI-PVBC Best performance is attained by the membranes with the highest PVBC content. These membranes enable to operate alkaline electrolyzers under mild conditions.